Effect of Planting Date and Variety of Cowpea [Vigna Unguiculata (L.)Walp.] on Green Pod Production - Ansoba, Y.E. (University of Ghana, 2013)
A study was carried out in 2012 in a Sudan savanna ecology in Ghana aimed at identifying the optimal planting dates and suitable cowpea varieties for green pod production. Six planting dates were considered starting from the onset of the rainy season (20th June, 30th June, 12th July, 25th July, 2nd August and 12th August), and four improved cowpea varieties released by Savanna Agricultural Research Institute (SARI) of the Council for Scientific and Industrial Research (CSIR) as Baawutawuta, Padi-tuya, Songotra and Zaayura. The experimental design used was a factorial Randomised Complete Block with five replications. Growth and yield parameters including plant height, stem diameter, number and weight of leaves, number and weight of branches, pods per plant, mean pod weight, pod diameter, pod length, leaf area, plant canopy and fibre content of the green pods were determined. Results indicated that the interaction effect of planting date and varieties on plant height was not significant during the early ages of plants but became significant from the fifth week onwards. Leaf area, pod diameter and fibre content of green pods were also significantly affected by interaction effect between variety and planting date. Pod length, pod number per plant and green pod yield per plant were not influenced by the interaction effect of planting dates and cowpea varieties but the different varieties responded differently to the different planting dates. The highest mean pod number per plant and green pod yield per plant did not follow the same trend as Baawutawuta recorded the highest mean pod number but was not the highest yielder per plant; while Padi-Tuya which did not produce the highest mean pod number per plant was the highest yielder per plant. The improved varieties proved to be suitable materials for green pod production but the date of planting for higher pod yield varied with variety considering the fact that Baawutawuta and Padi-Tuya produced highest pods per plant when planted on 12th August while Songotra and Zaayura recorded their highest number of pods per plant when planted on June 30th.
Thesis(MPHIL)-University of Ghana, 2013
Keywords: Planting; Cowpea; Green Pod